Complex solutions for nonlinear fractional partial differential equations via the fractional conformable residual power series technique and modified auxiliary equation method - Ali, Asghar; Nigar, Anam; Nadeem, Muhammad; Jat Baloch, Muhammad Yousuf; Farooq, Atiya; Alrefaei, Abdulwahed Fahad; Hussain, Rashida (Frontiers in Physics, 2023)
The fractional-order nonlinear Gardner and Cahn-Hilliard equations are often used to model ultra-short burst beams of light, complex fields of optics, photonic transmission systems, ions, and other fields of mathematical physics and engineering. This study has two main objectives. The main objective of this investigation is to solve the fractional-order nonlinear Gardner and Cahn-Hilliard equations by using the modified auxiliary equation method, which is not found in the literature. Secondly, the exact and approximate solutions of these equations are obtained by utilizing the fractional conformable Residual Power Series algorithm and the modified auxiliary equation method. For the analytical and numerical solutions to two equations, we employ two separate techniques, and we also establish consistency between the precise answers that we derive and the compatible numerical solution. This has never been investigated in this manner, to the best of our knowledge. The 2D and 3D contours have been defined using appropriate parametric values to support the results' physical compatibility. The assessed findings suggested that the approach used in this study to recover inclusive and standard solutions is approachable, efficient and faster in computing and can be thought of as a useful tool in resolving more complex phenomena that arise in engineering, mathematical physics and optical fiber.